1967
DOI: 10.1002/anie.196705811
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inorganic Systems at High Temperature by Mass Spectrometry

Abstract: High-temperature mass spectrometry (hitherto at temperatures between I000 and 2500 " K and at pressures between 10-3 and 10-12 atm) has already made possible the identiJication of many previously unknown and unpredicted diatomic and polyatomic molecular species. The present paper deals with the investigation of many oxides, of halides, and of carbon molecules and intermetallic molecules. An apparatus for the production and investigation of molecular beams is described. Knudsen cells permit the production of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(68 citation statements)
references
References 169 publications
2
65
0
1
Order By: Relevance
“…Mass spectrometric studies in high-temperature chemistry, aimed at the determination of thermodynamic properties for condensed phases and for gaseous molecules, mostly make use of Knudsen effusion (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]17,20,21,[24][25][26][27][28]) or of vapor transport supersonic molecular beam sampling methods (see, e.g., [15,19]) to generate the molecular beam that is to be analyzed with respect to the nature and the pressure of the gaseous chemical entities present in the cell containing the sample.…”
Section: Analysis Of Factors Determining Accuracymentioning
confidence: 99%
See 3 more Smart Citations
“…Mass spectrometric studies in high-temperature chemistry, aimed at the determination of thermodynamic properties for condensed phases and for gaseous molecules, mostly make use of Knudsen effusion (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]17,20,21,[24][25][26][27][28]) or of vapor transport supersonic molecular beam sampling methods (see, e.g., [15,19]) to generate the molecular beam that is to be analyzed with respect to the nature and the pressure of the gaseous chemical entities present in the cell containing the sample.…”
Section: Analysis Of Factors Determining Accuracymentioning
confidence: 99%
“…For diatomic molecules, such as H 2 , N 2 , O 2 , S 2 , Se 2 , Te 2 , and dimeric alkali halides, review of early measurements [5,8] had already shown that the cross-section is but ca. 50 % higher than for the atom or the monomer, rather than twice as large.…”
Section: Ionization Cross-sections Of Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its beginnings, the Knudsen Effusion Mass Spectrometry (KEMS) technique was recognized to be a powerful tool to discover new molecules and to investigate their energetic properties, such as dissociation and atomization energies [1]. In the last 50 years, many previously unknown molecular species were identified by KEMS in the high temperature vapors produced under conditions close to thermodynamic equilibrium, and their atomization energies determined.…”
Section: Introductionmentioning
confidence: 99%